Perancangan produk alat pengupas kulit dan pemipil biji jagung dengan Metode AHOQ di Kecamatan Silaen - Siagian, Wesly Mailander; Silaen, Willy Cristover; Prasetyo, Tegar Arifin; Maulana, Muhammad Ilham (Institut Seni Indonesia Yogyakarta, 2025)
The farmer group in the Silaen sub-district which is located in Toba Regency is a farmer group where the majority of farmers are corn farmers. The general problems faced by this farmer group include the ineffectiveness of the harvest process where farmers have to peel and dry the corn before the corn is ground using a corn sheller machine. Therefore, this research was carried out in order to answer the problems faced by this farmer group. Where in this research we will design a machine for peeling and shelling corn, so that farmers will be more practical when carrying out the harvest process. In this research, the Axiomatic House of Quality (AHOQ) method was used by integrating it with the House of Quality (HOQ) and Axiomatic design (AD). Then you will get a design and specifications for a corn peeling and shelling machine that uses an oil-fueled engine.